Huge magnetoresistance in topological insulator spin-valves at room temperature - Peng Tseng (Nature Portfolio, 2021)
Abstract Topological insulators (TI) have extremely high potential in spintronic applications. Here, a topological insulators thin-film (TITF) spin valve with the use of the segment gate-controlled potential exhibits a huge magnetoresistance (MR) value higher than 1000% at room temperature which is more than 50 times the MR of typical topological insulators (TI) spin-valves. A high spin-polarized current is provided by the band structure generated by the tunable segment potential. The results reveal a very large resistance difference between the parallel and antiparallel configurations. The MR effect is strongly influenced by the thin-film thickness, the gate potential, the gate size, and the distribution. The proposed results will help to not only improve the room-temperature performance of the spin-valves but also enhance the applications of magnetic memories and spintronic devices.